TANGGUNG JAWAB LINGKUNGAN DAN PERSEPSI ANCAMAN EKOLOGI TERHADAP PERILAKU PRO-LINGKUNGAN KARYAWAN PERUSAHAAN DI DAS CITARUM KECAMATAN BABAKANCIKAO KABUPATEN PURWAKARTA PROVINSI JAWA BARAT - istiana, rita (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
This study aims to measure the relationship between corporate environmental responsibility and the perception of ecological threats to the pro-environmental behavior of company employees. It was found that the environmental responsibility of the company had an effect on the pro-environment behavior of employees by 20.1%, which means that the role of the company to make rules or norms of pro-environment behavior was still very low. The perception of ecological threats has an effect on the pro-environment behavior of employees by 33.7%, this explains that employees’ knowledge of ecological threats is low and has not been able to provide awareness of the company’s environmental sustainability. The corporate environmental responsibility and the perception of ecological threats affect the pro-environment behavior of the company’s employees by 34.3%. These results can explain that the role of companies to educate their employees and the application of environmental preservation rules and norms needs to be further improved.